2019
DOI: 10.1111/aas.13522
|View full text |Cite
|
Sign up to set email alerts
|

Persistent severe post‐operative hypotension after pancreaticoduodenectomy is related to increased inflammatory response

Abstract: Background: Hypotension during major surgery is frequent, resulting in increased need for observation in the post-anaesthesia care unit and treatment including vasopressors and fluids. However, although severe hypotension in the immediate postoperative recovery phase after major surgery is suggested to be related to increased morbidity and mortality, the underlying risk factors are not well described, hindering advancements in prevention and treatment. Methods: We performed a retrospective study assessing fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the present retrospective cohort study, we found that the risk factors associated with IPH during PD were age, prolonged surgical procedures, more blood loss, and even more notably, decreased arterial Ca 2+ concentration. The incidence of IPH during PD was 41.42; similar to the report by Pitter and colleagues[ 11 ]. Our study confirms findings from previous studies, which indicated a close relationship of prolonged surgery and increased blood loss to intraoperative hypotension[ 4 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present retrospective cohort study, we found that the risk factors associated with IPH during PD were age, prolonged surgical procedures, more blood loss, and even more notably, decreased arterial Ca 2+ concentration. The incidence of IPH during PD was 41.42; similar to the report by Pitter and colleagues[ 11 ]. Our study confirms findings from previous studies, which indicated a close relationship of prolonged surgery and increased blood loss to intraoperative hypotension[ 4 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…The small arteries located anterior to the capillaries predominantly determine peripheral vascular resistance, which is influenced by the autonomic nervous system, self-regulation, endothelial-cell-derived molecules and inflammatory factors[ 10 ]. The increased inflammatory markers, such as C-reactive protein, can increase the risk for severe hypotension and vasopressor dependency during postoperative day 1 after PD[ 11 ]. A more positive fluid balance commonly seen in PD implicates inadequate circulating blood volume in the risk of IPH.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Consequently, the preoperative inflammatory status can be a major contributor to postoperative organ injury and therefore it is very important for risk stratification. 22,24 In addition, preoperative neuroendocrine responses to stress can modify the immune function and are associated with adverse outcomes, 25-28 while several drugs may induce inflammation or exert significant anti-inflammatory properties. 29-31 Therefore, preoperative suPAR levels may also assist in measuring inflammation, identifying a proinflammatory, inflammatory, or an immuno-suppressive status, which can influence short- and long-term outcome and/or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Blood loss was substituted with HA 5% or with blood transfusion if haemoglobin < 8.1 g/dL, according to national guidelines. 14 During the post-anaesthesia care unit (PACU) stay, the epidural infusion continued together with the GDT protocol, and NA if needed to maintain a MAP > 65 mmHg. PACU discharge followed standardized criteria.…”
Section: Anaesthesiologic and Surgical Protocolmentioning
confidence: 99%